Athlete Enjoyment of Prior Education Moderates change in Concussion-Reporting Intention after Interactive Education. (May 2021) - Daneshvar, Daniel H.; Baugh, Christine M.; Yutsis, Maya; Pea, Roy D.; Goldman, Shelley; Grant, Gerald A.; Cantu, Robert C.; Sanders, Lee M.; Chen, Christine L.; Lama, Roberto D.; Zafonte, Ross D.; Sorcar, Piya
Undiagnosed concussions increase risk of additional injuries and can prolong recovery. Because of the difficulties recognizing concussive symptoms, concussion education must specifically target improving athlete concussion reporting. Many concussion education programs are designed without significant input from athletes, resulting in a less enjoyable athlete experience, with potential implications on program efficacy. Athlete enjoyment of previous concussion education programs moderates the improvement in concussion-reporting intention after experiencing the research version of CrashCourse (CC) concussion education. Prospective cohort study. Level of evidence: Level IV. Quantitative assessment utilizing ANOVA with moderation analysis of 173 male high school football players, aged 13 to 17, who completed baseline assessments of concussion knowledge, concussion reporting, and attitudes about prior educational interventions. Athletes were subsequently shown CC, before a follow-up assessment was administered assessing the same domains. At baseline, only 58.5% of athletes reported that they enjoyed their previous concussion education. After CC, athletes were significantly more likely to endorse that they would report a suspected concussion (from 69.3% of athletes to 85.6%; P  < .01). Enjoyment of previous concussion education moderated concussion-reporting intention after CC ( P  = .02), with CC having a greater effect on concussion-reporting intention in athletes with low enjoyment of previous concussion education ( b  = 0.21, P  = .02), than on individuals with high enjoyment of previous concussion education ( P  = .99). Enjoyment of CC did not have a moderating effect on concussion-reporting intention. Athletes who previously did not enjoy concussion education exhibited greater gains in concussion-reporting intention than athletes who enjoyed previous education. Given the potential risks associated with undiagnosed concussions, concussion education has sought to improve concussion reporting. Because most athletes participate in concussion education programs due to league or state mandates, improving concussion-reporting intention in these low-enjoyment athletes is of particular relevance to improving concussion-reporting intention broadly.